Shafranov-shift destabilization of ballooning-type micro-instabilities - X. Jian; V. Chan; Z. Qiu; S. Ding; C. Holland; E. Bass; A. Garofalo; X. Liu (Nuclear Fusion, 2025)
Contrary to common wisdom, we argue that the Shafranov shift is destabilizing for the ambient ballooning-type instabilities, which account for most of the transport flux in tokamak core plasmas. Higher Shafranov shift indeed reduces the magnetic drift frequency ${ω _{\text{d}}}$ , i.e. improves the bad curvature mildly, around the outboard midplane. However, this improvement is limited to a very narrow spatial region while ${ω _{\text{d}}}$ is increased over the remaining poloidal space. The eigenfunction averaged $\langle {ω _{\text{d}}}\rangle $ is effectively enhanced due to the finite mode width of the eigenfunction and is thus destabilizing to the ballooning-type mode, as demonstrated by gyrokinetic simulations with the CGYRO code using local Miller equilibrium geometry. The predicted nonlinear flux also increases with Shafranov shift, consistent with linear simulations. The reduced transport model TGLF can capture the physics reasonably well.